LAS RELACIONES ENTRE LA UNION EUROPEA Y AMERICA LATINA: UN ANáLISIS DE LA ASOCIACIóN ESTRATéGICA BIRREGIONAL DESPUéS DE LA CUMBRE DE LIMA CON ESPECIAL REFERENCIA CENTROAMERICANA - Olmos Guipponi, María Belén (2015)
The article aims to analyze present andfuture relationships between the EuropeanUnion and Latin America in the light of recentdevelopments and new political, social andeconomic perspectives in both regions. Fromthe First Summit in Rio de Janeiro (1999) tothe last one (Lima, 2008) the bi-regional strategicassociation has gone through differentphases. In the current international situation,the Latin America region exhibits differentrealities with the Andean Community inthe throes of a crisis while MERCOSURis incorporating a new Member State, Venezuela.All the States forming part of SICAhave signed the DR-CAFTA with UnitedStates and are negotiating a new associationagreement with the EU. Within thiscontext Chile and Mexico have consolidatedtheir positions as single actors. Onthe other hand, the EU is also in the middle of a complex process, involving both élargissement(the incorporation of new MemberStates) and approfondissement (the signingand the ratification of the Lisbon Treaty). Relationsbetween the two regions are thus facingnew social, economic and political challenges.